Financial policy in developing countries - Heider Dawar (Intereconomics, 1976)
The present financial policies of the developing countries are hardly likely to create favourable conditions for economic growth. A change can only be brought about if the financing of development projects and the imports of consumer goods can be successfully integrated in an overall plan for economic growth and the generation of new sources of revenue for the state.
Keywords: 330; Development Financing